Quantum Size Effects in Thin Film Based on Lead Telluride - D. M. Freik; M. A. Ruvinskyy; O. B. Kostyuk; R. O. Dzumedzey (Фізика і хімія твердого тіла, 2016)
Based on the model of quantum flat rectangular and with infinitely high walls pit, the correspondences werecalculated and received value of the Fermi energy and kinetic coefficients (conductivity σ, Seebeck coefficient Sand thermoelectric power S2σ) for n-PbTe, by the Boltzman kinetic equation. Еhe cases with strongly degenerateand degenerate electronic gas in the films of lead telluride with n-type of conductivity are considered separately.The oscillating character of dependences of thermoelectric parameters of nanostructures based on n-PbTe for thedegenerate and strongly degenerate electron gas has been theoretically proved. Keywords: quantum size effect, thin film, lead telluride, thermoelectric properties.